APAKAH PENDIDIKAN KEWIRAUSAHAAN DIBUTUHKAN PADA ERA REVOLUSI INDUSTRI 4.0? - Sari Narulita; M Iswahyudi (Nusantara Hasana Berdikari, 2021)
This study aimed to determine the effect of entrepreneurship education on the emergence of interest in becoming entrepreneurs in students of the Vocational School (SMK) majoring in accounting in Banyuwangi. By using intervening variables perceived feasibility and perceived desirability as well as adding role models as moderating. The survey method using a questionnaire was used in this study. the research sample is there are vocational students in Banyuwangi accounting department. Data analysis using Partial Least Square (PLS) with warpPLS software version 3.0. the results of the study show that first, entrepreneurship education in vocational students majoring in accounting influences their interest in becoming entrepreneurs. Second, entrepreneurship education undertaken does not increase the interest of students to become entrepreneurs when through perceived feasibility and perceived desirability. Third, the role model added cannot strengthen the relationship between entrepreneurship education conducted with an interest in becoming entrepreneurs who through perceived feasibility and perceived desirabilty, but the role model is proven to strengthen the direct relationship between entrepreneurship education and interest in becoming entrepreneurs.